Diversity and profitability of oil palm smallholders in the southeastern Mexican states of Campeche and Tabasco - Patault Bertille; Penot Eric; Michel Isabelle; Cifuentes-Espinosa Jaime; Monzón-Alvarado Claudia; Feintrenie Laurene (Cahiers Agricultures, 2025)
Smallholders in southeastern Mexico face significant pedoclimatic constraints, including an uneven annual rainfall distribution and poorly workable soils. Consequently, they originally focused on extensive cattle rearing and food crops. Oil palm cultivation was introduced in the states of Campeche and Tabasco in the late 1990s via a federal rural development programme targeting family farmers. This article examines how smallholders have adopted oil palm cultivation and assesses the economic impacts of this shift. Technical-economic surveys were conducted in these states involving 47 oil palm producers and 8 interested farmers. Coexisting with agro-industrial estates and large cattle farms in the process of diversification, we differentiated two main types of smallholders: those specialising in oil palm cultivation and larger producers (>50 ha) who diversified into oil palm while remaining cattle ranchers. Our results show that oil palm cultivation is economically more attractive than alternatives such as cattle rearing, maize cultivation or agricultural wage labour. The study area can be divided into three agroecological zones with varying palm oil production potentials, influencing technical practices and economic performance. We identified three types of oil palm cropping systems based on input and labour use: the “extensive”, the “intermediate”, and the “intensive” ones. In a context of volatile palm oil prices, our results indicate that the “intermediate” system yielded the highest labour and per-hectare productivity, in all agroecological zones. All smallholder oil palm farms generated high revenues and positive cash balances, enabling self-financed expansion of at least two hectares annually.